(untitled) (Modern education and development, 2025)
The article examines how artificial intelligence technologies can be used in the study of English Romanticism. English Romanticism is an important period of literature of the 18th and 19th centuries, which presents ideas such as nature, the human psyche, fantasy, and freedom. Artificial intelligence, in particular, through the use of natural language processing, data analysis, and generative models, helps to automate the analysis of romantic works, create new literary works, and gain a deeper understanding of the historical context. The article highlights the possibilities of using AI for methodological and semantic analysis of texts, creating advanced search systems in literary studies, and identifying literary motifs of the Romantic period.